2005
DOI: 10.1152/physrev.00016.2004
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of CLCA Proteins

Abstract: CLCA proteins were discovered in bovine trachea and named for a calcium-dependent chloride conductance found in trachea and in other secretory epithelial tissues. At least four closely located gene loci in the mouse and the human code for independent isoforms of CLCA proteins. Full-length CLCA proteins have an unprocessed mass ratio of ∼100 kDa. Three of the four human loci code for the synthesis of membrane-associated proteins. CLCA proteins affect chloride conductance, epithelial secretion, cell-cell adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
126
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(130 citation statements)
references
References 209 publications
(382 reference statements)
3
126
0
Order By: Relevance
“…While intelectin has been previously implicated in immunity to nematodes [6], the demonstration of a secreted CLCA protein in response to parasite challenge is novel. CLCA proteins are putative Ca 2+ -activated Cl -channels or channel regulators but have also been shown to affect epithelial secretion, cell-cell adhesion, apoptosis, cell cycle control, and mucus production (for review, see [16,30]). hCLCA1 and mCLCA3 (alias gob-5) are distributed in mucin producing goblet cells [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While intelectin has been previously implicated in immunity to nematodes [6], the demonstration of a secreted CLCA protein in response to parasite challenge is novel. CLCA proteins are putative Ca 2+ -activated Cl -channels or channel regulators but have also been shown to affect epithelial secretion, cell-cell adhesion, apoptosis, cell cycle control, and mucus production (for review, see [16,30]). hCLCA1 and mCLCA3 (alias gob-5) are distributed in mucin producing goblet cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…CLCA proteins are putative Ca 2+ -activated Cl -channels or channel regulators but have also been shown to affect epithelial secretion, cell-cell adhesion, apoptosis, cell cycle control, and mucus production (for review, see [16,30]). hCLCA1 and mCLCA3 (alias gob-5) are distributed in mucin producing goblet cells [16]. Recent studies have shown that all subunits of hCLCA1 and mCLCA3 are secreted soluble proteins rather than being trans-membrane proteins [7,23].…”
Section: Discussionmentioning
confidence: 99%
“…16 Furthermore, interactions between chloride and various amino acid sidechains are responsible for chloride ion selectivity and transport in various ion channels including the ClC type. [17][18][19][20] The present study provides new insights into how the local chloride binding environment is manifested in the chlorine CS tensor.…”
Section: Introductionmentioning
confidence: 99%
“…16 Furthermore, interactions between chloride and various amino acid sidechains are responsible for chloride ion selectivity and transport in various ion channels including the ClC type. [17][18][19][20] The present study provides new insights into how the local chloride binding environment is manifested in the chlorine CS tensor.Another major thrust of the present work is to determine how sensitive the chlorine EFG and nuclear magnetic shielding tensors are to the local molecular structure surrounding the chloride ions, specifically the positions of the protons to which they are hydrogen-bonded. Ashbrook and Duer have recently described in detail how structural information may be extracted from solid-state NMR experiments performed on quadrupolar nuclei.…”
mentioning
confidence: 99%
“…In the absence of specific pharmacological modulators, the identification of the ion channel(s) underlying this current is an important first step necessary for the development of tools designed to study this phenomenon. Members of three families of proteins have been shown to induce I Cl(Ca) when expressed in heterologous cellular systems: calcium-activated chloride channels (CLCAs), bestrophins and members of the tweety gene family (for reviews see [4,[7][8][9]16] ). In order to assess these molecules as candidates underlying sensory neuron I Cl(Ca) we analyzed expression of members of the 3 families by RT-PCR on normal and axotomized DRGs.…”
Section: Introductionmentioning
confidence: 99%